2020
DOI: 10.1039/c9fo02357g
|View full text |Cite
|
Sign up to set email alerts
|

Rosmarinic acid alleviates ethanol-induced lipid accumulation by repressing fatty acid biosynthesis

Abstract: Rosmarinic acid ameliorates ethanol-induced lipid accumulation by reducing fatty acid biosynthesis and tumor necrosis factor-α.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…15,22–24 For example, rosmarinic acid ameliorates ethanol-induced injury in the mouse hepatocyte cell line (AML12) by anti-lipid accumulation, anti-oxidative stress, and anti-inflammation. 25 It displays hypolipidemic effects in orotic acid-induced non-alcoholic fatty liver disease rat model rats. 26 It also protects rats against streptozotocin-induced hyperlipidemia, oxidative stress, inflammation, and tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…15,22–24 For example, rosmarinic acid ameliorates ethanol-induced injury in the mouse hepatocyte cell line (AML12) by anti-lipid accumulation, anti-oxidative stress, and anti-inflammation. 25 It displays hypolipidemic effects in orotic acid-induced non-alcoholic fatty liver disease rat model rats. 26 It also protects rats against streptozotocin-induced hyperlipidemia, oxidative stress, inflammation, and tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the network pharmacology analysis, a total of 17 active components of SGN were screened out, and the drug-component-target network model was constructed; the key active components were mainly isofraxidin, astilbin, and rosmarinic, caffeic, neochlorogenic, and chlorogenic acid. Previous studies have demonstrated that rosmarinic acid and astilbin exhibit various pharmacological activities, such as anti-inflammatory ( Chu et al, 2012 ), hepatoprotective ( Guo et al, 2020 ), and anti-oxidative activities ( Sharma et al, 2020 ; Wang et al, 2020 ). Phenolic compounds, including neochlorogenic, chlorogenic, cryptochlorogenic, and caffeic acid, can treat metabolic syndrome since they exert anti-oxidative, anti-inflammatory, and antilipidemic effects ( Banjari et al, 2017 ; Santana-Galvez et al, 2017 ; Zhao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since ancient times, RA has been used in folk medicine, cosmetics, and dietary supplements. The health-promoting benefits of RA could be based on scavenging reactive oxidation species, decreasing nitric oxide production, lipid peroxidation, increasing high-density lipoprotein, decreasing low-density lipoprotein levels, and deranged hemolysis (Baba et al 2004 ; Guo et al 2020 ). Nyandwi et al ( 2021b ) has reported lipid-lowering effects of RA through modulation of reverse cholesterol transport-related proteins, thereby combating hyperlipidemia-based disorders.…”
Section: Pharmacological Properties Of Ramentioning
confidence: 99%